The history of pneumococcal conjugate vaccine development: dose selection. (December 2013) - Poolman, Jan T; Peeters, Carla CAM; van den Dobbelsteen, Germie PJM
Pneumococcal conjugate vaccines (PCVs) differ in polysaccharide (PS) dose, carrier protein and conjugation method. PCV development proceeded initially upon principles successfully proven in Haemophilus influenzae type b (Hib) conjugate vaccine development. However, the need to successfully incorporate multiple serotypes while minimizing the total PS dose and total carrier protein load saw some early vaccine candidates fail. Dose–range studies of individual serotypes indicated that much lower PS doses were needed compared with Hib conjugate vaccines, although subsequent studies confirmed that lower Hib PS doses were possible. Furthermore, the immune response to individual serotype doses was carrier protein dependent. A 'one-size fits most' approach has characterized PS dose selection, but peculiarities of individual serotypes are increasingly apparent, raising the question whether re-formulation of PCVs to maximize individual serotype performance is needed.